2004
DOI: 10.1614/ws-03-030r
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for allelopathic interference of Japanese honeysuckle (Lonicera japonica) to loblolly and shortleaf pine regeneration

Abstract: Japanese honeysuckle presents a serious problem to the economically attractive natural regeneration of loblolly and shortleaf pine. This research investigated the potential allelopathic interference mechanisms of Japanese honeysuckle in relation to pine regeneration and growth, which may provide insight into overcoming this problem. The allelopathic potential of root exudates and leaf litter from Japanese honeysuckle was tested against loblolly and shortleaf pine seedlings. When Japanese honeysuckle and loblol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…These compounds are similarly the source of allelopathic interactions among plants (Inderjit and Keating 1999), and indeed, allelopathic interactions have been implicated in the spread and invasiveness of several exotics (Callaway and Bais et al 2003;Kogar and Bryson 2004;Prati and Bossdorf 2004;Skulman et al 2004, Vivanco et al 2004). Indeed, Inderjit and Keating (1999) list 112 weedy species, including many of those on the database used for this study and those cited above, as plants shown to have allelopathic activities.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are similarly the source of allelopathic interactions among plants (Inderjit and Keating 1999), and indeed, allelopathic interactions have been implicated in the spread and invasiveness of several exotics (Callaway and Bais et al 2003;Kogar and Bryson 2004;Prati and Bossdorf 2004;Skulman et al 2004, Vivanco et al 2004). Indeed, Inderjit and Keating (1999) list 112 weedy species, including many of those on the database used for this study and those cited above, as plants shown to have allelopathic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Allelopathy has been suggested as a mechanism for exotic plant invasion in many species (Lawrence et al 1991;Roberts and Anderson 2001;Bais et al 2003;Hierro and Callaway 2003;Skulman et al 2004). L. maackii is an important invader in the eastern and midwestern U.S., but the potential for direct chemical effects of L. maackii on neighboring plants has been little studied.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, incorporation of Lonicera japonica (Japanese honeysuckle) leaves into soil reduced the growth of loblolly and shortleaf pine, an effect that may be related to several phenolic secondary metabolites found in the tissues (Skulman et al 2004). In the other study, Trisel (1997) showed that aqueous extracts of L. maackii leaves could reduce the germination of green ash and sugar maple.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second major colonization event hypothesized by was that extensive growth of L. japonica in response to greater light effectively allows it to form a new ground layer, which may suppress the reproduction of overstory dominants and kill small trees and shrubs. The rapid development of populations of L. japonica may also result from its allelopathic effects on trees (Skulman et al 2004) and herbs Friedland and Smith 1982;Davison and Forman 1982). Suppression of dominant species may lead to positive feedback that converts the forest to an open vine-dominated disclimax (Little 1961;Whigham 1984).…”
Section: Hybridsmentioning
confidence: 99%